Roots and branches [compact disc] - Trower, Robin (V-12 Records, 2012)
Robin Trower pays homage to his early influences, and demonstrates his guitar mastery on new material too. Tracks included: Hound Dog, and The Thrill Is Gone, and Shape of Things to Come.